Teen pregnancy. Study in Acobamba - Huancavelica. 1998 - Villón, Juan (2015)
OBJECTIVE: To determine the incidence and clinical and epidemiological characteristics of pregnant adolescents seen in birth, CS Acobamba Huancavelica in 1998. DESIGN: A retrospective study of pregnant teenagers was conducted. RESULTS: an incidence of 16% was found, all related to late adolescence (15-19 years). Most came from rural areas (65%), with primary education (55%) and unstable union with their partners (100%). 70% had their menarche between 12 and 14 years and 20% started their sexual activity before age 15. 15% had been previously pregnant. 40% never received prenatal care and who did started late, especially in the third quarter (50%). 40% presented complications during pregnancy and delivery, postpartum no; these were prolonged labor (50%), perineal tears (25%), premature rupture of membranes and preterm delivery (12.5%). In newborns 10% had low birth weight and prematurity 5%; 35% of asphyxia and no suffocated minute to 5 minutes. CONCLUSIONS: Poor level of general education, early onset of sexual intercourse and little or no use of contraceptive methods are associated with a high incidence of teenage pregnancy; the prolonged labor, perineal tears, products with low birth weight and prematurity are common in adolescents.